The state of Philippine business education - Salazar, Melito Jr. S. (Philippine Journal of Public Administration, 1985)
In a nationwide survey of business firms and schools offering business programs, it was found among other things that: business education programs are geared towards producing specialists in specific fields especially accounting, business administration, banking and finance; the faculty of business schools are underpaid considering their qualifications and job effort; there has been an increasing student enrolment in the masteral and doctoral programs although the bulk of students are still in the undergraduate degree programs; and traditional teaching facilities like the use of blackboards and visual aids still predominate. The study also cited that business schools draw their major strengths from highly qualified, trained and experienced faculty, students who are attuned to local business conditions, and reasonable tuition fees. Identified as top five weaknesses, on the other hand, were inefficient professors, loose admission standards, theoretical method of instruction, lack of English proficiency of students, and schools unable to tap the business sector as partners in training students. Some recommendations are made: (1) strengthen and establish linkages between and among business schools and business organizations, (2) emphasize entrepreneurship and small business development and, (3) establish a technical panel for business education at the MECS to rationalize and improve Philippine business education.